Kilka uwag o Komisji dla spraw oszczędności państwowych z 1920 r. - Przygodzki, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article is devoted to the fi rst committee to improve the administration during the period of the Second Republic of Poland — Commission for Matters of State Savings of 1920. It was established by the government of Wincenty Witos, and its chairman was the Interior Minister Stanisław Wojciechowski. The aim of the Commission was to present proposals to simplify public administration, reduce the number of offices and officials and unify the efficiency of the entire administration. However, the results of the work of this committee were minor. At the beginning of 1921 Prime Minister Witos decided to dissolve the Commission.
Keywords: II Rzeczpospolita; reforma administracji; rząd Wincentego Witosa; Komisja do Spraw Oszczędności Państwa 1920; administracja II RP